Achievement motive of future physical education teachers - Lazarević Dušanka; Trebješanin Biljana (Zbornik Instituta za pedagoška istraživanja, 2007)
This paper presents the results of the research of the characteristics of achievement motive of future physical education teachers. Starting from understanding of the importance of achievement motive for the successful accomplishment of professional goals and roles of teachers, the aim of our research is to examine the level of achievement motive, the characteristics of its structure and differences according to gender. The instrument MOP2002 (Franceško et al., 2002a) was applied, which presupposes the complex structure of this motive. The sample consisted of 373 students (263 male and 110 female) of the Faculty of Sport and Physical Education in Belgrade. The results show that their achievement motive is characterized by the tendency towards high level of presence, and its structure is in the largest degree determined by the components accomplishing goals as a source of pleasure and perseverance in accomplishing goals, which is followed by orientation towards planning. The component competing with others is demonstrated in a moderate degree and it is least expressed. It was shown that female students have a larger degree of achievement motive when compared to male students, and accomplishing goals as a source of pleasure and perseverance in accomplishing goals mostly contribute to the difference in structure of achievement motive. It can be expected that the achievement motive, with the structure and degree of presence determined in our respondents, will contribute that they, as future teachers, become a good motivational model and the creators of a desirable motivational climate.